1977
DOI: 10.1002/app.1977.070210724
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low temperatures on polymorphic structures of cotton cellulose

Abstract: SynopsisEffects of low temperatures upon fine structures of cotton pretreated with either liquid ammonia or caustic of mercerizing strength were investigated. Temperatures of cotton after impregnation with liquid ammonia were lowered by (1) liquid nitrogen, (2) acetone-Dry Ice, (3) acetone, or (4) simple evaporation. With alkali-impregnated fabrics, temperature was lowered by immersion in liquid nitrogen. Changes in fine structure of ammonia-and alkali-celluloses were evaluated by x-ray diffraction before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Regarding the crystalline structures of cellulose, they are classified into four crystallization types, viz. cellulose I, II, III, and IV, and their crystalline structures can be transformed from one type to another 19. Figure 4 shows the X‐ray diffraction pattern of the pure BC and BC/collagen composite.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the crystalline structures of cellulose, they are classified into four crystallization types, viz. cellulose I, II, III, and IV, and their crystalline structures can be transformed from one type to another 19. Figure 4 shows the X‐ray diffraction pattern of the pure BC and BC/collagen composite.…”
Section: Resultsmentioning
confidence: 99%
“…The crystalline structure of cellulose is classified into four types, namely cellulose I, II, III, and IV. Their crystalline structures are able to transform from one to another type. , Figure a shows the X-ray diffractograms of cellulose pulp and cellulose regenerated from DMAc/LiCl solvent system. Cellulose pulp exhibited typical cellulose I structure with X-ray diffraction peaks at 15, 16.8, and 23° assigned to (110), (1-10) and (200), respectively .…”
Section: Resultsmentioning
confidence: 99%
“…The degree of conversion to III increases as the temperature is lowered from ambient to as low as liquid nitrogen [ 10], but complete conversion does not occur at atmospheric pressure. At elevated pressures, the degree of conversion of I to III is increased.…”
Section: Resultsmentioning
confidence: 99%
“…These low degrees of conversion to III were obtained on several cotton varieties of various micronaires in the sliver form. Our initial investigations of the effects of temperature on the conversion of I to III by liquid ammonia at atmospheric pressure indicated that the degree of conversion to III increased as the temperature decreased [ 10]. The greatest conversion to III was obtained when liquid ammonia was removed with liquid nitrogen (-196°C).…”
mentioning
confidence: 99%